2016
DOI: 10.1158/0008-5472.can-16-0980
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Chemoresistance Relies on the Stem Cell Reprogramming Factor PBX1

Abstract: The evolution of chemoresistance is a fundamental characteristic of cancer that ultimately defeats its clinical management. However, it may be possible improve patient outcomes significantly by defeating nodal resistance mechanisms which cancers rely upon during the evolution to an untreatable state.Here we report an essential role for upregulation of the stem cell reprogramming factor PBX1 in mediating chemoresistance in recurrent ovarian carcinomas. In clinical specimens, high levels of PBX1 expression corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 38 publications
2
73
1
Order By: Relevance
“…5, we clearly demonstrated that c-Kit upregulates phospho-PHB Y259 in the lipid raft domain to interact with the membrane-tethered Notch3 fragment and enhance the Notch3-PBX1 signaling pathway in ovarian cancer cells. However, whether this increase in PBX1, a stem cell reprogramming factor in ovarian cancer chemoresistance [39], is Fig. 8 Downregulation of raft-phospho-PHB Y259 reduces tumorigenic ability and sensitizes tumors to carboplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, we clearly demonstrated that c-Kit upregulates phospho-PHB Y259 in the lipid raft domain to interact with the membrane-tethered Notch3 fragment and enhance the Notch3-PBX1 signaling pathway in ovarian cancer cells. However, whether this increase in PBX1, a stem cell reprogramming factor in ovarian cancer chemoresistance [39], is Fig. 8 Downregulation of raft-phospho-PHB Y259 reduces tumorigenic ability and sensitizes tumors to carboplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Phospho-PHB Y259 in the membrane raft is required for the c-Kit-mediated activation of Notch3, PBX1, β-catenin and ABCG2 Activation of Notch signaling pathways might upregulate the downstream targets of Notch, such as PBX1, to drive the stemness and carcinogenesis of cancer [38,39]. We thus examined the effects of c-Kit on Notch3 and PBX1 in SKOV3 cells.…”
Section: Metastatic Phenotypes Of Skov3 In Xenograft Murine Ascites Smentioning
confidence: 99%
“…Therefore, there is no doubt that PBX1 promotes PCa cell proliferation, survival, and chemoresistance. Actually, a recent study showed that ovarian cancer chemoresistance relies on PBX1 overexpression (12). Our recent study has demonstrated that PBX1 promotes the expression of oncogenic RNF6, thus increasing leukemia chemoresistance to doxorubicin (3).…”
Section: The Usp9x/pbx1 Axis In Prostate Cancer Chemoresistancementioning
confidence: 96%
“…PBX1 has been demonstrated to confer to chemoresistance in both breast cancer (12) and leukemia (3), but it was not well known in PCa. To determine the expression profile of PBX1 in PCa, a panel of prostate tissues from patients with benign prostate hyperplasia (BPH), prostatic intraepithelial neoplasia (PIN), or primary PCa was evaluated by immunohistochemical (IHC) assays.…”
Section: Pbx1 Is Highly Expressed In Pca Tissues and Is Associated Wimentioning
confidence: 99%
See 1 more Smart Citation